The Magnitude and Determinants of Suboptimal Child Spacing Practices Among Women of Childbearing Age in Ethiopia: A Systematic Review and Meta-Analysis - Abebaw Alamrew; Mulat Ayele; Eyob Shitie Lake; Getinet Kumie; Haimanot Hailu; Aynalem Yetwale; Tadele Emagneneh; Chalie Mulugeta (Women's Health Reports)
Background: Short birth intervals (SBI), also known as suboptimal childbirth intervals, are frequent and have detrimental effects on both mother and child health. There is limited national data except for small-scale studies on the prevalence and contributing factors of SBI practices in Ethiopia. We did this review to find the pooled prevalence of suboptimal birth spacing and its contributing factors among Ethiopian women of reproductive age. Methodology: This study followed the PRISMA guideline. Articles were found using MEDLINE/PubMed, Scopus, Hinari, Google Scholar, and Web of Science. Subgroup analysis was used to look for heterogeneity evidence. I2 statistics and funnel plots with the Egger test were used to assess the studies’ heterogeneity and publication bias. Results: In total, 19 studies were included in this meta-analysis with a sample size of 11,674. The pooled prevalence of SBI was 50.29% (95% confidence interval [CI], 43.18, 57.40). Rural residency (adjusted odds ratio [AOR] = 2.13; 95% CI: 1.19, 3.07), age at first marriage less than 18 (AOR = 1.94; 95% CI: 1.34, 2.54), women with no formal educational status (AOR = 3.39; 95% CI: 2.59, 4.19), no contraceptive use (AOR = 4.20; 95% CI: 2.84, 5.56), duration of breastfeeding less than 24 months (AOR = 3.44; 95% CI: 1.64, 5.25), female sex of the index child and survival (death) of the index child (AOR = 2.34; 95% CI: 1.53, 3.15), and (AOR = 2.17; 95% CI: 1.02, 3.31), respectively, were the main determinants of suboptimal child spacing. Conclusion: The pooled prevalence of suboptimal child spacing practices in Ethiopia was found to be high almost half of the births were suboptimal.